KERAGAMAN PENGHAYATAN KRISTOLOGIS DALAM ALKITAB - Prisna Pritalora; Elsa Oktavia; Sarmauli Sarmauli (CV. ADIBA AISHA AMIRA, 2025)
This research aims to explore the diversity of Christological understandings in the Bible and its implications for the understanding of Christ in the context of globalization. In an atmosphere of pluralism and interfaith dialogue, the main challenge faced is how to understand Christ inclusively while remaining faithful to His original teachings. The research methodology used is a qualitative approach, which includes literature studies, in-depth interviews with theologians and religious leaders, as well as observations in ecumenical contexts. The findings indicate that various Christological understandings influence how Christians interact with broader society and shape their faith identity. Additionally, this study highlights the importance of interfaith dialogue in building a harmonious and inclusive Christological understanding. Thus, the diversity of Christological perspectives not only enriches theological insight but also provides practical guidance for addressing social and cultural challenges in the modern era.